Konseling Gizi Meningkatkan Pengetahuan dan Asupan Gizi Ibu Hamil - Nadimin Nadimin; Agustian Ipa; Rudy Hartono; Nabilah Rihadatul Aisy (Direktorat Politeknik Kesehatan Makassar, 2024)
A common nutritional problem among pregnant women is macro and micronutrient deficiencies manifested in chronic energy deficiency (CED). The prevalence of CED among pregnant women in Indonesia is still quite high. Counseling aims to increase the knowledge of pregnant women who will form good nutrition fulfillment behavior. The purpose of the study was to determine the effect of nutrition counseling on the knowledge and intake of pregnant women with CED. Pre-experiment research design with one-group pre-test post-test design. This study was conducted in the Bontoa Health Center Area of Maros Regency for three weeks. The sampling technique was the purposive sampling technique. The sampling was 10 pregnant women who had an upper arm circumference below 23.5 cm. Data on knowledge level was collected through the pre-post test. Data on intake was collected before and during the intervention three times using 24-hour food recall. The effect of counseling on the knowledge of pregnant women was analyzed using the Wilcoxon test, while the effect of counseling on the intake of pregnant women using the Paired Sample T-test test. The results of statistical analysis showed that there was a difference in knowledge before and after counseling (p=0.005). The difference in the intake of pregnant women before and after counseling in energy intake (p=0.000), protein (p=0.007), fat (p=0.035), and carbohydrates (p=0.001). Likewise, the intake of vitamin C (p=0.022) and iron (p=0.017). This study concludes that the implementation of nutrition counseling for three weeks can improve knowledge and intake in pregnant women with CED.